Small granule protein CP2 of Cryptosporidium translocates to the parasite-host interface during invasion and localizes to parasitophorous vacuole membrane in association with other secretory proteins - Yang, Fuxian; Huang, Yujin; Zhu, Ping; Zhang, Shengchen; Huang, Jilei; Chen, Haoyu; Gong, Xiaoqing; Guo, Yaqiong; Li, Na; Xu, Rui; Feng, Yaoyu; Xiao, Lihua (PLOS Pathogens, 2026)
Cryptosporidium is a major cause of diarrhea in humans and farm animals for which there are no effective drugs. The parasite resides in a parasitophorous vacuole on the surface of gastrointestinal epithelial cells. Although the parasitophorous vacuole membrane (PVM) plays a critical role in parasite development and survival, its composition and biogenesis are not well understood. In this study, we used reverse genetic tools to investigate the secretion and function of a potential PVM protein called CP2. Endogenous gene tagging revealed that, following biosynthesis, CP2 is stored in the small granules (SG) within sporozoites. Upon invasion of host cells, CP2 is translocated to the parasite-host interface. During intracellular development, CP2 is distributed across the entire PVM in trophozoites and microgamonts, but it is concentrated in the lower PVM, near the attachment zone, in mature meronts and macrogametes. Interestingly, CP2 is dispensable; deleting the CP2 gene did not significantly affect the growth or pathogenicity of a virulent Cryptosporidium strain. CP2 knockout resulted in increased expression of a neighboring gene encoding SG3, which is also translocated from the SG to the PVM. SG3 was further localized to knob-like and filamentous structures outside the PVM. Together, these findings suggest that CP2 is secreted to the parasite-host cell interface during invasion and intracellular growth, where it potentially contributes to the formation of the nascent parasitophorous vacuole of Cryptosporidium, together with other SG proteins.